Inter-religious Conflict, Translation, and the Usage of the Early Modern Notion of "Religion" from the Fall of Constantinople to the Westphalian Peace Treaty in 1648 - Reeh, Niels (Journal of religion in Europe, 2020)
The article attempts to show that the modern notion of "religion" is a construction that emerged in the context of inter-religious encounters following the fall of Constantinople and especially in the years around the Reformation. Hereby, the article argues that the modern notion of "religion" emerged earlier than found by most previous studies, and that it was used in the legislation of the new Protestant states as well as in the modern (Westphalian) state-system, both of which it has been a part of ever since. The notion of "religion" is, thus, not a scholarly invention (J.Z. Smith) or tied to colonialism (Timothy Fitzgerald) but rather a product of complex historical processes in which religious conflicts and the attempt to overcome these played a key role.